KERJA PEMBEBANAN DAN TEMPERATUR TERHADAP SUSUT UMUR TRANSFORMATOR TENAGA 150/20 kV 60 MVA - Juara Mangapul Tambunan; Agung Hariyanto; Wahyu Kurniadi Tindra (Sutet, 2015)
In Indonesia have been in the design of a transformer with an environmental temperature of 2000C and operate around 3000C, so a working transformer must be adapted to the load. Shrink age transformer affected by isolation transformer oil and transformer entanglement. Excessive heat can damage the transformer coil insulation and temperature rise on oil can change the viscosity of the oil transformer. In the observations of work load and temperature on the Power Transformer lead shrink age and ability of the smaller the transformer supplying the load is also on the wane. The increase will raise the temperature of the load end of the hot-spot, which is approaching the maximum allowable value. From observations obtained temperature hot-spot only reached 107.180C, then your age will increase the transformer of 1.3891 years. So according to the calculation, the transformer on a GI Kembangan can operate for 20.55 years according the IEEE when coupled with the age 1.3891 years, then the transformer will be 21.9391 year. To date, Transformers GI Kembangan has been operating for 13 years so the rest of the transformer is expected to become age 8.9391 years.